"Quick-chatting", "smart dogs", and how to "say without saying": Small talk and pragmatic learning in the community. (February 2015) - Yates, Lynda; Major, George
Abstract: In this paper we focus on the perspectives and practical needs of a group of adult immigrants from language backgrounds other than English as they encounter the pragmatic demands of communicating in the workplace and in the community. Drawing on a subset of data from a large-scale longitudinal study of recent adult immigrants with low levels of English, we explore what they notice about the pragmatics of communication in Australia and the sociopragmatic and pragmalinguistic skills they need to 'fit in' and function successfully through English. The pragmatic issues they identify encompass a range of sociopragmatic and pragmalinguistic issues not normally addressed in interlanguage research, including the importance of small talk and how to participate in it, the role and interpretation of informality and indirectness, different perceptions of sociability and the 'need to be nice', recognition of the need to be pragmatically flexible, and differences between the language taught in the classroom and that used every day in the community. We consider the implications for language classes in an ESL setting and suggest some activities designed to help immigrants prepare for the transition from classroom language learner to competent language user in the community.